Society 5. 0 : A Transformation Towards Human-Centered Artificial Intelligence. - Acharya, Biswa Ranjan (CRC Press, 2025)
The book will help the readers in the field of the Internet of Things, and especially its convergence with artificial intelligence, which has given rise to the new paradigm of artificial intelligence of things (AIoT). It covers important concepts such as intelligent space and human-centered robotics and its effect on human wellbeing, and human-centered aviation automation.This book: Supports the advancement in artificial intelligence and the Internet of Things used in societal applications. Discusses the role of modeling human factors in designing smart systems as highlighted in Industry 4.0. Covers big data scheduling and the global standard method applied to smart maintenance. Presents human-centered aviation automation, human-centered processes, and decision support systems. Highlights the importance of data privacy and secure communication in society 5.0. The text is primarily written for senior undergraduate, graduate students, and academic researchers in diverse fields including electrical engineering, electronics and communications engineering, computer science and engineering, and information technology.
Keywords: Internet of things.; Artificial intelligence.; elektronické knihy; electronic books